Variant selection and macrozone in Ti-6Al-4V walls during laser hot wire direct energy deposition - Rajib Halder; Souvik Sahoo; Jake T. Benzing; Alec I. Saville; Anthony D. Rollett (Journal of Materials Research and Technology)
Additively manufactured Ti-6Al-4V (Ti64) wall structures used as various structural aerospace components suffer from the spatial variations in mechanical properties, texture-mediated anisotropy, and macrozones that degrade the mechanical performance, especially fatigue, under certain service conditions. The development of texture and macrozone formation in α/β titanium alloys are closely related to the variant selection during the β→α phase transformation in the additive manufacturing process. In this study, electron backscatter diffraction (EBSD) was employed to investigate the variant selection mechanism and macrozone formation criteria in single- and multi-wall specimens manufactured with laser hot wire directed energy deposition (LHW-DED). Variant analysis revealed that strong variant selection with a preferred selection of the type 2, <112¯0>/60° variant occurs in both single and multiwalls. The primary factor dictating the selection of the α/α variant boundaries was found to be the cooling rates. The main underlying mechanism governing variant selection to compensate for β→α transformation strain during solid-state phase transformation was determined to be the triple-alpha variants clustering of Category I. Evidence of thermal stress playing a minor role in variant selection was also observed. Furthermore, location-specific variant analysis revealed that the white bands (microstructural bands with distinct etching contrast) on the walls consist of fewer α variants than the bulk. The macrozones formation criteria are proposed and the effect of macrozones on mechanical behavior is discussed in conjunction with the Schmid factor analysis of α variants with respect to different loading directions. The density of macrozones was also quantified.